The Role of Different Monocyte Subsets in the Pathogenesis of Atherosclerosis and Acute Coronary Syndromes. (September 2015) - Idzkowska, E.; Eljaszewicz, A.; Miklasz, P.; Musial, W. J.; Tycinska, A. M.; Moniuszko, M.
Abstract The inflammation underlying both atherosclerosis and acute coronary syndromes is strongly related to monocyte‐related actions. However, different monocyte subsets can play differential roles in the formation and destabilization of atherosclerotic plaque as well as healing of damaged myocardial tissue. Monocytes are currently being divided into three functionally distinct subsets with different levels of CD14 (cluster of differentiation 14) and CD16 expression. Thus, there are classical CD14++CD16‐, intermediate CD14++CD16+ and non‐classical CD14+CD16++ monocytes. Here, we summarize the current knowledge on complex activities of different monocyte subsets in atherosclerosis and acute coronary syndromes. Moreover, we discuss which monocyte subsets can serve either as predictive biomarkers of cardiovascular risk or as potential targets used in atherosclerosis and its complications.